Overview Of Cases Of Violence Against Women And Children In Gunung Jati General Hospital, Cirebon City In 2021-2022 - Rusman, Andri Andrian; Dwi S, Putri Meida; Nurlaela, Lutfhi (Sean Institute, 2024)
Violence against women and children is an increasing phenomenon, but often these cases are not accurately reported. This study aims to identify the characteristics of cases of violence against women and children at Gunung Jati General Hospital, Cirebon City in 2021-2022. Using secondary medical record data, this study was conducted retrospectively with a cross-sectional design. The results showed that the majority of victims were girls aged 11-15 years, not yet working, from Cirebon City, and the perpetrators of violence were generally known people. Sexual violence was the most common type of violence experienced by child victims. These findings indicate the importance of attention to the prevention, handling, and assistance of victims of violence, with the P2TP2A unit of Cirebon City expected to increase these efforts.